Extracellular Vesicles from Amnion-Derived Mesenchymal Stem Cells Ameliorate Hepatic Inflammation and Fibrosis in Rats - Masatsugu Ohara; Shunsuke Ohnishi; Hidetaka Hosono; Koji Yamamoto; Kohei Yuyama; Hideki Nakamura; Qingjie Fu; Osamu Maehara; Goki Suda; Naoya Sakamoto (Stem Cells International)
Background. There are no approved drug treatments for liver fibrosis and nonalcoholic steatohepatitis (NASH), an advanced stage of fibrosis which has rapidly become a major cause of cirrhosis. Therefore, development of anti-inflammatory and antifibrotic therapies is desired. Mesenchymal stem cell- (MSC-) based therapy, which has been extensively investigated in regenerative medicine for various organs, can reportedly achieve therapeutic effect in NASH via paracrine action. Extracellular vesicles (EVs) encompass a variety of vesicles released by cells that fulfill functions similar to those of MSCs. We herein investigated the therapeutic effects of EVs from amnion-derived MSCs (AMSCs) in rats with NASH and liver fibrosis. Methods. NASH was induced by a 4-week high-fat diet (HFD), and liver fibrosis was induced by intraperitoneal injection of 2 mL/kg 50% carbon tetrachloride (CCl4) twice a week for six weeks. AMSC-EVs were intravenously injected at weeks 3 and 4 in rats with NASH (15 μg/kg) and at week 3 in rats with liver fibrosis (20 μg/kg). The extent of inflammation and fibrosis was evaluated with quantitative reverse transcription polymerase chain reaction and immunohistochemistry. The effect of AMSC-EVs on inflammatory and fibrogenic response was investigated in vitro. Results. AMSC-EVs significantly decreased the number of Kupffer cells (KCs) in the liver of rats with NASH and the mRNA expression levels of inflammatory cytokines such as tumor necrosis factor- (Tnf-) α, interleukin- (Il-) 1β and Il-6, and transforming growth factor- (Tgf-) β. Furthermore, AMSC-EVs significantly decreased fiber accumulation, KC number, and hepatic stellate cell (HSC) activation in rats with liver fibrosis. In vitro, AMSC-EVs significantly inhibited KC and HSC activation and suppressed the lipopolysaccharide (LPS)/toll-like receptor 4 (TLR4) signaling pathway. Conclusions. AMSC-EVs ameliorated inflammation and fibrogenesis in a rat model of NASH and liver fibrosis, potentially by attenuating HSC and KC activation. AMSC-EV administration should be considered as a new therapeutic strategy for chronic liver disease.